The Effectiveness of Digital-Based Islamic Religious Education Learning Media on the Formation of Noble Morals for Children Aged 5-6 Years at the State Kindergarten of Samporoa - Fadila, Fitri; Nurhayati, Nurhayati; Awalunisah, Sita; Dorrutunnisah, Dorrutunnisah (Journal of Educational Sciences, 2025)
The integration of digital-based media has become an effective approach to enhance the interactivity and attractiveness of learning, including in Islamic education. This study investigates the effectiveness of digital media in fostering noble character among early childhood learners. A quantitative method with a descriptive experimental approach was employed, using observations, interviews, documentation, and assessment instruments for data collection. The data were analyzed through descriptive and inferential techniques.The findings demonstrate that the application of digital learning media significantly improved children’s character development at Pembina Samporoa State Kindergarten. Before the intervention, none of the children were categorized as Developing Very Well, but this increased to 30.55% afterward. The Developing as Expected category also rose from 36.11% to 41.66%. In contrast, the Starting to Develop and Not Developing categories decreased from 49.99% to 22.21% and from 13.88% to 5.55%, respectively. A paired sample test confirmed the significance of these results, with a value of 9.644 > 1.795885 and a significance level of 0.01 < 0.05, indicating that Ho was rejected and HI accepted. Overall, the study confirms that infocus-based digital media effectively supports the formation of noble character in early childhood, highlighting its potential to strengthen Islamic character education.